2018
DOI: 10.1186/s40170-018-0180-9
|View full text |Cite
|
Sign up to set email alerts
|

Beta-hydroxybutyrate (3-OHB) can influence the energetic phenotype of breast cancer cells, but does not impact their proliferation and the response to chemotherapy or radiation

Abstract: BackgroundKetogenic diets (KDs) or short-term fasting are popular trends amongst supportive approaches for cancer patients. Beta-hydroxybutyrate (3-OHB) is the main physiological ketone body, whose concentration can reach plasma levels of 2–6 mM during KDs or fasting. The impact of 3-OHB on the biology of tumor cells described so far is contradictory. Therefore, we investigated the effect of a physiological concentration of 3 mM 3-OHB on metabolism, proliferation, and viability of breast cancer (BC) cells in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 111 publications
(103 reference statements)
5
27
0
Order By: Relevance
“…Ketone bodies cannot be used as an alternative energy fuel in cells with defective mitochondria 12,25 . Previous studies demonstrated that glioma cells cannot use ketone bodies and that ketone bodies do not stimulate tumour growth 56,57 . Hence, the KD-R has a dual function in (1) targeting glucose-dependent signaling pathways that drive tumour growth, and (2) in providing an alternative metabolic fuel to normal brain cells under glucose restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Ketone bodies cannot be used as an alternative energy fuel in cells with defective mitochondria 12,25 . Previous studies demonstrated that glioma cells cannot use ketone bodies and that ketone bodies do not stimulate tumour growth 56,57 . Hence, the KD-R has a dual function in (1) targeting glucose-dependent signaling pathways that drive tumour growth, and (2) in providing an alternative metabolic fuel to normal brain cells under glucose restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Yuan et al has shown that multiple mutations in mtDNA may render compromised OxPhos function ( 142 ) thus pushing the cell toward glycylysis. On the other hand, several studies have shown that glycolytic tumors can not metabolize fatty acid and ketone bodies ( 230 , 250 , 251 ) for energy production. Individual mitochodnria are genetically heterogenous due to large copy number of the genome, each copy may have different mutations.…”
Section: Conclusion: Cscs Eradication By Targeting Its Metabolismmentioning
confidence: 99%
“…This is problematic for these cells because they frequently lack metabolic flexibility. On the one hand, many studies have found that tumor cells display decreased expression of ketolytic enzymes,81, 82, 83, 84, 85 although more recently a few counterexamples were discovered 6 , 7 . On the other hand, a large part of a solid tumor would consist of hypoxic areas in which oxygen concentrations are too low to efficiently metabolize ketone bodies and fatty acids, even if the necessary enzymes would be expressed 86 .…”
Section: Discussionmentioning
confidence: 99%
“…KDs are very low carbohydrate, high fat diets that mimic certain characteristics of fasting, in particular through reduction of plasma insulin with an accompanying elevation of the ketone bodies acetoacetate and β-hydroxybutyrate. The state of nutritional ketosis in adults is typically characterized by concentrations of β-hydroxybutyrate in the range 0.5–3 mmol/l 5 and glucose in the range 85–95 mg/dl 6 . However, with concurrent calorie restriction much lower blood glucose concentrations (55–80 mg/dl 7 ) can be achieved, resulting in a higher ketone-to-glucose ratio.…”
Section: Introductionmentioning
confidence: 99%